1997
DOI: 10.1002/(sici)1097-0231(199709)11:14<1596::aid-rcm998>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the chromium oxygenated cluster ions produced during the laser ablation of chromium oxides by laser ablation/ionization Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Trivalent and hexavalent chromium oxides have been examined by time-of-flight laser microprobe mass spectrometry and Fourier transform ion cyclotron resonance mass spectrometry (FTICRMS). The positive-ion spectra show a strong correlation with the valency of chromium in the oxide. Thus, the positive cluster ion distribution and the presence of characteristic chromium cluster ions allow us to distinguish the two oxides. Metallic compounds present in industrial environments have been widely studied over the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…This ion was previously described in work by Aubriet et al 29 The next observed set, dichromium oxide clusters Cr 2 O + at 120 amu and Cr 2 O 2 + at 136 amu were also calculations indicate that all of the observed intermetallic clusters are thermodynamically favorable, therefore, their presence in the mass spectrometer is an rational result. Given the high temperatures in the laser ablation process, the relative magnitudes of the exoergicity are not expected to be manifested in the ratio of peak heights.…”
Section: Metal Oxide Clusterssupporting
confidence: 67%
“…This ion was previously described in work by Aubriet et al 29 The next observed set, dichromium oxide clusters Cr 2 O + at 120 amu and Cr 2 O 2 + at 136 amu were also calculations indicate that all of the observed intermetallic clusters are thermodynamically favorable, therefore, their presence in the mass spectrometer is an rational result. Given the high temperatures in the laser ablation process, the relative magnitudes of the exoergicity are not expected to be manifested in the ratio of peak heights.…”
Section: Metal Oxide Clusterssupporting
confidence: 67%
“…In the projectile category, Gianotto and Groenewold investigated a variety of aluminum, silicon, and chromium oxides, generating small-to-medium sized cluster ions with rhenium tetroxide (ReO 4 -) as the projectile. 46-53 Laser ablation is more commonly used, and Aubriet [54][55][56][57][58] and Gaumet [59][60][61][62][63] have used it for forming alumina, silica, and d-block oxyanions. Laser irradiation has also enjoyed extensive use for forming metal oxide clusters by targeting the laser on a rotating metal rod as pioneered by several groups, [64][65][66][67][68][69][70][71] enabling study of a wide variety of transition metal oxides; this approach tends to form hypo-oxidized species, and the extent of oxidation can be manipulated by seeding the ablation region with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…In that case molecular oxygen as well as metallic cation could be in their ground or excited states. 15 The two former processes of MO þ ion formation have been already suggested for transition metals 15,27 and for lanthanide compounds. 28 Moreover, Willson et al 28 have proposed another way of MO þ formation-chemiionization-when lanthanides are ablated in oxygen reactive atmosphere.…”
Section: Examination Of M þ and Mo þ Ion Formation With M ¼ B Ca And Gdmentioning
confidence: 88%
“…Note that most of the experiments are performed with the total or partial ejection of the major ion (Ca þ , BO 2 À ) in order to enhance the detection of the signal delivered by mixed oxygenated cluster ions. 15 The (partial or total) ejection of abundant ions in our experimental procedure allows the abundance of large cluster ions to be increased without any loss of information. Indeed, ejection of a high concentration of a single type of ion from the ICR cell often enhances signal because of reduced Coulomb ejection of other ions.…”
Section: Methodsmentioning
confidence: 99%